Vivências de cuidadores familiares no cuidado ao idoso em tratamento quimioterápico ambulatorial - Perrando, Miriam da Silveira (2015)
Population aging is a global reality. Increasing life expectancy is a fact in developing countries due to technological and scientific advances. Associated with longevity, throughout the aging process, the individual may experience non-communicable chronic diseases such as cancer. The occurrence of cancer is related to situations of fragility, possibly causing elderly dependency for the conduction of their care. In such dependency, it is highlighted the importance of the role of a family caregiver. The following study has been guided by the research question: how is the experience of elderly care in outpatient cancer chemotherapy from the perspective of family caregivers? It also aimed to describe the experiences of family caregivers in the care of elderly patients with cancer receiving outpatient chemotherapy. It is a qualitative, descriptive, and exploratory study conducted in a large hospital in the state of Rio Grande do Sul. The study participants were 12 family caregivers of elderly in outpatient chemotherapy. In compiling the data, the Sensitive Creative Method has been applied, through three dynamics of creativity and sensitivity linha da vida , tecendo estórias , and almanaque . In order to analyze the data, it has been applied French Discourse Analysis. From the analysis it emerged a category that generated eight themes and seven sub-themes. The results showed that the experience of family caregivers permeates the clashes related to disclosure or not of the diagnosis of the disease to the elderly; the monitoring of changes in the elderly's health condition, such as addiction care. They have also experienced the situation of independency and autonomy to self care of some elderly. The life of family caregivers has changed in their routine to take care of the elderly. However, caring for the elderly is seen as an opportunity to repay the care received by them in other stages of life. The experience revealed difficulties faced by family caregivers in getting access to public health services for tests and treatment for elderly people with cancer. The experience of caregivers is permeated by the infantilization of attitude of preconceived ideas about aging and the elderly/old age. Family members also realize that cancer experienced by the elderly gets the family closer to the finitude of life and the positivity of events presented by the elderly represent resilience in the face of illness. The study allowed the approach to the theme of elderly care with cancer at home and also the understanding of the particularities in family relationships against the illness of the elderly. It is expected that the study may bring contributions to critical reflections on family homecare of the elderly.